Isolation of enterobacteria in some molluscs of the Peruvian sea - Taboada P., Dora A. (1974)
In this paper, it has given to know the result of a bacteriologic study on 5 species of mollusk used as human food, they were: Aulacomya ater, Gari sp., Mesodesma donacium, Aequipecten purpuratus and Thais chocolata; they were from several markets of Callao and Lima. It was isolated Salmonella enteritidis serotype Derby and Edwardsiella of Gar¡ sp. Others bacteria os Proteus, Citrobacter, Enterobacter and Serrotia were presents too. AII the mollusks were contamined by E. coli.